Soil Chemical Properties of Silver Fir and Spruce Forest Under Different Systems of Silviculture. I-Changes in Soil Nitrogen - Gupta, M. K.; Singh, R. P.; Jha, M. N. (Indian Forester, 1989)
Silvicultural management practices have differential impact on soil properties according to the system followed. An investigation was carried out in Picea smithiana and Abies pindrow forests managed under selection, shelterwood and clearfelled systems in Kotgarh Forest Division (H.P.) to quantify the differences in soil nitrogen status at different sites in the three management systems. Inter-correlation between total and available nitrogen, correlation of nitrogen status with soil depth in all the conditions have been reported Soils under selection system showed higher nitrogen accumulation followed by shelterwood and clearfelled systems. Soil nitrogen showed significant negative correlation with depth in all sites and management systems. A vailable and total nitrogen showed significant positive correlation in all sites and management systems.